Artificial intelligence reviewing academic work : an unorthodox proposition? - Zopiatis, Anastasios (My University, 2026)
Following the dramatic increase in manuscript submissions to peer-reviewed journals and the scarcity of qualified reviewers, among other challenges, editors are struggling to maintain the academic integrity and viability of their publications. The recent pandemic has exacerbated the problem, necessitating the adoption of a new approach for evaluating academic work within the context of the peer-review system. Recent advances in AI technologies have led to a significant rise in the use of such tools by academia, despite skepticism — especially regarding integrity and robustness — and may provide substantial capabilities for reviewing academic work. Reflecting on the above, the primary purpose of this conceptual study is to explore the potential use of AI technology in reviewing academic papers in the ‘Publish or Perish’ era. Among other issues, the study examines current AI capabilities, with an emphasis on the advantages and disadvantages in reviewing academic work, the possible challenges associated with this endeavor, and its likely future applications. The findings, of importance to academic scholars, aim to expand our horizons as to the potential of such technologies for academia.
Keywords: Artificial intelligence (AI); Peer review process; Publish or Perish; Conceptual paper